Network Radar Countermeasure Systems Integrating Radar and Radar Countermeasures - Jiang, Qiuxi (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This is the very first book to present the network radar countermeasure system. It explains in detail the systematic concept of combining radar and radar countermeasures from the perspective of the information acquisition of target location, the optimization of the reconnaissance and detection, the integrated attack of the signals and facilities, and technological and legal developments concerning the networked system. It achieves the integration of the initiative and passivity, detection and jamming. The book explains how the system locates targets, completes target identification, tracks targets and compiles the data.